The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijms22158327
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of CCCH Zinc-Finger Proteins in Plant Abiotic Stress Tolerance

Abstract: Zinc-finger proteins, a superfamily of proteins with a typical structural domain that coordinates a zinc ion and binds nucleic acids, participate in the regulation of growth, development, and stress adaptation in plants. Most zinc fingers are C2H2-type or CCCC-type, named after the configuration of cysteine (C) and histidine (H); the less-common CCCH zinc-finger proteins are important in the regulation of plant stress responses. In this review, we introduce the domain structures, classification, and subcellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 198 publications
3
53
0
Order By: Relevance
“…Several studies have shown that CCCH proteins are involved in stress tolerance in plants [ 57 ]. For example, Arabidopsis AtSZF1 and AtSZF2 , two closely related CCCH zinc finger genes, negatively regulate the expression of salt-responsive genes and modulate the tolerance to salt stress [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that CCCH proteins are involved in stress tolerance in plants [ 57 ]. For example, Arabidopsis AtSZF1 and AtSZF2 , two closely related CCCH zinc finger genes, negatively regulate the expression of salt-responsive genes and modulate the tolerance to salt stress [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the number and order of the Cys and His residues that bind the Zinc ion in the secondary structure of the finger, they were divided into several different types, including C2H2, C2C2, C2HC, C2C2C2C2, and C2HCC2C2 [ 7 , 8 , 9 ]. Among the different zinc-finger proteins, Cys2/His2 (C2H2)-type (TFIII-types) was a characteristic representative of eukaryotic transcription factors to abiotic stress [ 10 , 11 , 12 , 13 , 14 , 15 ]. Di19 (drought-induced 19) protein containing two typical Cys2/His2 zinc finger domains is one of the Cys2/His2-type TFs.…”
Section: Introductionmentioning
confidence: 99%
“…The positive regulatory roles of bHLH transcription factors have been shown in different plants [ 65 ]. Our data analysis revealed higher expression of a gene encoding zinc finger C3H domain-containing protein 53 (cluster-30086.92972) in T03R than T22R ( Figure 5 and Table S13 ), suggesting that this gene might be a contributor to salinity tolerance in guar [ 66 ]. We observed upregulation of a gene (cluster-30086.34639) encoding an MYB transcription factor in T03R compared to C03R in response to salinity ( Figure 5 and Table S13 ).…”
Section: Discussionmentioning
confidence: 99%